1 µm range InGaPAs three-dimensional islands grown by molecular beam epitaxy. (December 2020) - Andryushkin, V V; Gladyshev, A G; Babichev, A V; Kolodeznyi, E S; Novikov, I I; Karachinsky, L Ya; Nevedomskii, V N; Egorov, A Yu
Abstract: A new technique allowing growing three-dimensional InGaPAs islands with reduced surface density by molecular beam epitaxy is proposed. The structural and optical properties of the islands have been studied depending on the InGaP layer thickness, the substrate temperature, and exposure time in the arsenic flow. The estimated island density was about 1.3 · 10 10 cm −2 .